Obesidade e fatores de risco na população de 20 a 59 anos de Feira de Santana-Ba, 2007 - Mascarenhas, Morgana Teixeira Lima (2010)
Obesity is a public health illness in world-wide level, the one that is associates of: escolarity, age, income, race and others. A pathology of considerable incidence in which had present time, over all, to the modification of alimentary habits and the sedentarism. The obese individuals finish, in function of the search for the ideal weight, developing alimentary upheavals, the most frequent upheaval of periodic alimentary compulsion (TCAP). To evaluate the prevalence of obesity and the factors of risk (sociodemografic and mannering) and esteem the prevalence of alimentary upheavals had constituted objective of this study, transversal cut, descriptive character, between 2.506 participants, of 20 the 59 years of age, both the sex. In order to characterize the population-target, it was used frequency and the prevalence as measured of occurrences and the reason of prevalence, to verify the associations between the 0 variable. Significant association between obesity and autorefered illnesses was observed. The prevalence of alimentary upheavals (You) was of 1,00% for nervous bulimia (BN) and 5,03 % for upheaval of periodic alimentary compulsion (TCAP). The prevalence of both the upheavals was bigger in the feminine sex, in the age band of 20 the 29 years. The association of the corporal image with the two types You was statistically significant (p<0, 001) in both the sex. The upheavals had revealed prevalence in the black race and obese individuals. The results of the research point the intervention necessity, mainly of being able them public, with sights to the control of this "epidemic" that comes serving to compose gradual indices of morbidity and mortality the population, of the risks the one that if display when of the wild search for the lose of weight. Special attention must be given for identification of upheavals in the women who if find in the age band of 20 the 29 years.